The transcriptional regulator YY1 binds to the 5'-terminal region of B19 parvovirus and regulates P6 promoter activity. - Momoeda, M (1994)
We performed a systematic study to identify cellular factors that bound to the terminal repeat region of B19 parvovirus. Using electrophoretic mobility shift assays, we detected one cellular factor which prominently bound to the repeat region. The factor was purified from K562 nuclear extract by specific DNA affinity column chromatography and identified as YY1, a multifunctional transcription factor. Of multiple possible YY1 binding sites in the upstream region of the P6 promoter, three showed specific strong binding. Transcription enhancement by YY1 was demonstrated in vitro by transient transfection assays. In studies using truncated and mutated versions of this region, YY1 activity was diminished by the alteration of any two of these three sites and abolished by the alteration of all three sites. Our results suggest that YY1 is a positive regulator of B19 parvovirus transcription.